Analisis Biaya Diferensial dalam Membuat Keputusan Menerima atau Menolak Pesanan Khusus pada CV. Ali Sukses 99 - Valentina Monoarfa; Febri Setiyawati; Hendriyanto Pembengo (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the application of differential cost analysis in making decisions to accept or reject special orders at CV. Ali Sukses 99. The research method used is descriptive qualitative with data collection through interviews and direct observation. The research results show that cost factors that must be considered, such as raw material costs, labor and factory overhead, are very influential in decision making. Through a special order case study in April 2024, it was found that the revenue generated exceeded variable costs, resulting in significant contribution profits. This shows the importance of differential cost analysis in making profitable decisions for the company. The decision to accept custom orders proves that this strategy can increase a company's profitability.